2011
DOI: 10.1007/s00380-011-0209-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of chronic kidney disease and anemia after percutaneous coronary intervention in acute myocardial infarction patients

Abstract: Anemia is a common complication of chronic kidney disease (CKD), and a few studies suggest that both CKD and anemia have a marked impact on the prognosis of patients with cardiovascular disease. We retrospectively analyzed the prevalence of CKD and anemia in 312 patients with acute myocardial infarction (AMI). The patients were divided into four groups according to the presence of CKD and anemia. Chronic kidney disease was defined as estimated glomerular filtration rate <60 ml/min/1.73 m(2), and anemia was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…In contrast, other studies suggest that whilst these relationships exists for unadjusted data, anaemia is no longer associated with increased mortality following adjustment for potential confounders such as age, comorbidity burden and procedural demographics, (16,(21)(22)(23), MACE (11,23)or ischemic complications (2). Other studies have also suggested an independent association with mortality only in males but not females (1).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, other studies suggest that whilst these relationships exists for unadjusted data, anaemia is no longer associated with increased mortality following adjustment for potential confounders such as age, comorbidity burden and procedural demographics, (16,(21)(22)(23), MACE (11,23)or ischemic complications (2). Other studies have also suggested an independent association with mortality only in males but not females (1).…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have reported conflicting data regarding the association between anaemia and clinical outcomes in patients undergoing PCI, with studies reporting both an independent association with increased mortality, MACE and major bleeding complications (3,5,(8)(9)(10)(15)(16)(17) or no increase in risk following adjustment for differences in age, comorbidity burden and procedural demographics (9,21,22), or only associated with poorer outcomes in patients with severe anaemia but not mild or moderate anaemia (11). Other studies have suggested that post-procedural anaemia is independently associated with MACE (23).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] On the other hand, cardiorenal anemia syndrome, in which the simultaneous presence of CKD, anemia, and heart failure creates pathological reciprocal connections, thereby resulting in an adverse synergistic impact on morbidity and mortality, is now attracting more attention. 7,8) However, few data are available concerning the impact of CKD and anemia on clinical outcomes among AMI patients undergoing primary percutaneous coronary intervention (PCI) in Japan, 9,10) and in terms of CKD concomitant with anemia, only the recent report from Matsue and colleagues has examined the longterm prognostic impact of CKD/anemia combination after hospital discharge in Japanese AMI patients. 10) network for heart diseases in Kyoto.…”
mentioning
confidence: 99%
“…7,8) However, few data are available concerning the impact of CKD and anemia on clinical outcomes among AMI patients undergoing primary percutaneous coronary intervention (PCI) in Japan, 9,10) and in terms of CKD concomitant with anemia, only the recent report from Matsue and colleagues has examined the longterm prognostic impact of CKD/anemia combination after hospital discharge in Japanese AMI patients. 10) network for heart diseases in Kyoto. 11) The purpose of the present study was therefore to examine the prognostic impact of admission CKD and admission anemia on PCI results and in-hospital outcomes in Japanese AMI patients undergoing primary PCI, using data from the AMI-Kyoto Multi-Center Risk Study.…”
mentioning
confidence: 99%
“…26) Acute decompensation of HF may cause acute impairment of renal function. "Cardiorenal syndrome" is present in up to one-third of patients with HF and is related with prolonged hospitalization and worse survival.…”
Section: Discussionmentioning
confidence: 99%